Pengembangan Modul Asam Basa Makanan Berbasis Learning Cycle 5E untuk Meningkatkan Hasil Belajar Siswa SMP Kota Bengkulu - Delvi Putriana; Meirita Sari (Kilau Publishing, 2026)
Science learning in schools is still dominated by the use of textbooks and lecture methods, so students’ involvement in the learning process is not yet optimal. This condition affects students’ conceptual understanding, especially in acid–base material which is abstract in nature. This study aimed to develop and analyze the quality of a science module based on the Learning Cycle 5E on the topic of food acids and bases in terms of design, feasibility, practicality, and effectiveness. This research used a Research and Development (R&D) method with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were ninth-grade students of SMP IT Khairunnas Bengkulu City. The research instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests in the form of pretest and posttest. The data were analyzed using quantitative descriptive analysis and statistical tests with the help of SPSS. The results showed that the module was systematically arranged according to the stages of Engage, Explore, Explain, Elaborate, and Evaluate. The validation results indicated that the module was categorized as very feasible in the material aspect (82.08%) and language aspect (82.59%), and feasible in the media aspect (80.78%). The practicality of the module was shown through the teacher response of 100% and student responses in small and large group trials of 86.97% and 88.62%, respectively, both categorized as very good. The effectiveness of the module was indicated by an increase in the students’ average score from 69.90 in the pretest to 92.37 in the posttest with a significant difference. In addition, the N-Gain analysis result of 0.75, which falls into the high category, indicates a substantial improvement in learning outcomes after using the module. Therefore, the Learning Cycle 5E–based module is considered feasible, practical, and effective in improving students’ learning outcomes on the topic of food acids and bases.